Cytoplasmic gene expression: lessons from poxviruses. Issue 10 (October 2022) - Grimm, Clemens; Bartuli, Julia; Fischer, Utz
Abstract : In eukaryotic cells, the process of gene expression is confined to the nucleus and enabled by multisubunit RNA polymerases (RNAPs). Many viruses make use of the host cellular gene expression apparatus during infection, and hence transfer their genome at least transiently to the host nucleus. However, poxviruses have evolved a different strategy to propagate. Their double-stranded DNA genome is transcribed in the host cytoplasm by a virus-encoded RNAP (vRNAP), which is evolutionarily related to eukaryotic RNA polymerase II. In this Review, we highlight recent high-resolution structures of the poxviral transcription apparatus in different phases of action. These structures, along with biochemical data, now allow the definition of a comprehensive model of poxviral gene expression and its regulation. Highlights: Poxviruses possess a unique transcription system that works independently from the host nuclear transcription apparatus. The poxviral mRNA is co-transcriptionally capped and polyadenylated and hence can be converted into protein by the translation system of the host. Single particle cryo-electron microscopy has enabled insight into atomic details of the poxviral transcription apparatus and its phylogenetic origin. The enzymatic core of the poxviral transcription system is homologous to eukaryotic multisubunit polymerases, but accessory factors deviate vastly in their function and architecture. Recently solved structures revealed poxviral transcription intermediates that have not (yet) been observed for nuclear polymerases. Structures of poxviral transcription intermediates are attractive targets for rational drug design.